MODERN CONCEPT OF CHILDREN’S PRESCHOOL EDUCATION: CHANGES AND CHALLENGES - Malinauskienė, Daiva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article deals with a modern concept of children’s preschool education and scientific research meant to substantiate a positive impact of high-quality preschool education on a child’s life and his/her academic achievements in future. The analysis of foreign and national sources, research and strategic documents on education focusing on the evaluation of essential changes in the sector of preschool education and the discussion of the prospects of institutional preschool education has been conducted. The issues that must inevitably become a part of the work schedule of the Lithuanian education policy have been distinguished: accessibility of educational institutions, high quality (self-)education, the necessity of help for a child belonging to a risk group, ensuring education and social services for families and children in poverty, education of talented and gifted children, the situation of (self-)education of children in rural areas and other issues that are important for the practice of children’s (self-)education of today.